Legal Protection for Consumers for Damage to Goods by Sea - Delsfie Adelia Rauf (Estudiante Law Journal, 2022)
Abstract: This study aims to determine Legal Protection for Consumers for Damage to Goods by Sea. The method used in this study is empirical legal research methodology and uses a qualitative approach to descriptive qualitative analysis techniques. The results of this study indicate that legal protection for consumers for damage to goods by sea, there are several things, namely the protection provided by the expedition in the form of responsibility for losses suffered by the consumer. This responsibility is in the form of providing compensation for damaged goods while being transported by our expedition, in this case, PT MAE Cargo Gorontalo. In addition, there are forms of legal protection provided by consumer protection regulations, including those contained in Article 7 letter f of the consumer protection law by imposing business actors to provide compensation and compensation for goods received by consumers in a damaged condition.